NECROTIZING FASCIITIS – CASE REPORT AND REVIEW OF THE LITERATURE - Yungareva, I.Ch.; Nikolov, V.V.; Marina, S.S. (Інфекційні хвороби, 2013)
Necrotizing fasciitis (NF) is a severe soft tissue infection characterized by necrosis of the skin, subcutaneous tissue and fascia. This rare condition carries high mortality rate and require prompt diagnosis and urgent treatment includes broad-spectrum antibiotic coverage, hemodynamic support, nutritional supplements, wound care, and surgical debridement. We describe a case of 63-year old man who presented with the history of diffuse erythema, edema, pain on the lower leg 4 days before hospitalisation. Initially he was admitted and treated for erysipelas but later was diagnosed as necrotizing fasciitis which was successfully treated with no ill effects what so ever from this devastating condition. Paucity of cutaneous findings early in the course of the disease makes diagnosis challenging. Prompt surgical debridement, intravenous antibiotics, fluids and electrolytes management and analgesia are mainstays of the therapy. Adjuvant treatments like clindamycin, hyperbaric oxygen therapy and intravenous immunoglobulins are discussed.